2017
DOI: 10.18632/oncotarget.21244
|View full text |Cite
|
Sign up to set email alerts
|

Genetic or pharmacologic inhibition of EGFR ameliorates sepsis-induced AKI

Abstract: Despite recent studies have demonstrated that the EGF receptor (EGFR) activation provided a renoprotective role during ischemic and folic acid-induced AKI, the role and regulation mechanism of EGFR in septic AKI remains unclear. Here, gefitinib, a highly selective EGFR inhibitor, abrogated LPS-induced phosphorylation of EGFR, ERK1/2, and STAT3 as well as expression of COX, eNOS, and proinflammatory cytokines in HK-2 cells. In addition, c-Src is an upstream of EGFR signaling pathway and mediates LPS-induced EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…CDDP: cisplatin; GL: Ganoderma lucidum; EOD: every other day; EGFR: epidermal growth factor receptor. 9 Oxidative Medicine and Cellular Longevity potential for AKI during endotoxemia and diabetic nephropathy [74,75]. Our results showed that the upregulation of EGFR, following CDDP injection, was significantly downregulated in rats treated with GL, and this correction was associated with the improvement that occurred in nephrotoxicity indices.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…CDDP: cisplatin; GL: Ganoderma lucidum; EOD: every other day; EGFR: epidermal growth factor receptor. 9 Oxidative Medicine and Cellular Longevity potential for AKI during endotoxemia and diabetic nephropathy [74,75]. Our results showed that the upregulation of EGFR, following CDDP injection, was significantly downregulated in rats treated with GL, and this correction was associated with the improvement that occurred in nephrotoxicity indices.…”
mentioning
confidence: 61%
“…EGFR may mediate renal injury by induction of inflammatory factors and cell apoptosis. However, inhibition of EGFR showed therapeutic potential for AKI during endotoxemia and diabetic nephropathy [ 74 , 75 ]. Our results showed that the upregulation of EGFR, following CDDP injection, was significantly downregulated in rats treated with GL, and this correction was associated with the improvement that occurred in nephrotoxicity indices.…”
Section: Discussionmentioning
confidence: 99%
“…The animal experiments were performed according to the rules approved by the animal ethics committee from Central South University. The HK-2 cells were as previously described (12,13).…”
Section: Van-induced Aki Modelmentioning
confidence: 99%
“…If the detailed information of our animal model is fully utilized and discussed, it will provide more basic data for future research. The existing research about the LPS concentrations in cell experiments ranges from 50 ng/ml to 10 μ g/ml [ 28 , 29 ] and the duration ranges from 30 minutes to 48 hours [ 29 , 30 ]. According to our experimental results, 30 μ g/ml LPS and culture duration of 6 h were selected for the cell model.…”
Section: Discussionmentioning
confidence: 99%